The Effect of Group Guidance Simulation Game Technique to Improve Emotional Intelligence of Students of Class X-RPL SMK Negeri 10 Semarang - Wahyuni, Ira Lelly; Kusdaryani, Wiwik; Maulia, Desi (Jurnal Indonesia Sosial Sains, 2024)
This research investigates the effect of group guidance using simulation game techniques to improve the emotional intelligence of students in Class X-RPL at SMKN 10 Semarang. This study uses an experimental pre-test and post-test control group design. Based on the results of research conducted on class X - RPL students at SMKN 10 Semarang, it was concluded that group guidance services using simulation game techniques affected increasing emotional intelligence. This is proven by the results of the experimental group questionnaire, which obtained an increase in the mean or average score from the pretest of 57.6 to the posttest of 63.11, in other words, an increase of 9.5%. Furthermore, the T-test results obtained a sig (2-tailed) value of 0.001. This means that providing treatment with group guidance and simulation game techniques has a significant influence on increasing the emotional intelligence of class X-RPL students at SMKN 10 Semarang.